Factors contributing to demand for life reinsurance in Malaysia / Walter Jenggi - Jenggi, Walter (2010)
The purpose of this research is to investigate the factors that contribute to the demand for life reinsurance in Malaysia. The research method used is the Ordinary Least Square regression inflation rate, gross domestic product per capita, size, and taxation. Model. There are four independent variables that are included in this research which is These four independent variables will be examined in order to identify their relationship with the demand for life reinsurance in Malaysia. In this study, the data are based on secondary data collected from Annual Insurance Report compiled by Bank Negara Malaysia and also some data from International Monetary which available on www.economywatch.com. These data are obtained for a ten years period from 1999 to 2008. The results from the findings shows that there is a relationship between all variables with demand for life reinsurance but only independent variable size has a significant relationship with the demand for life reinsurance in Malaysia.